Front Cover: Development of Fluorophosphoramidate as a Biocompatibly Transformable Functional Group and its Application as a Phosphate Prodrug for Nucleoside Analogs (ChemMedChem 17/2022). (7th September 2022) - Yoshida, Yuki; Zheng, Ti; Tanabe, Wataru; Tomoike, Fumiaki; Hashiya, Fumitaka; Suzuki, Tetsuro; Hirota, Shuto; Saiki, Yuriko; Horii, Akira; Hirayama, Akiyoshi; Soga, Tomoyosi; Kimura, Yasuaki; et al.
Abstract : The Front Cover shows a new type of biocompatible phosphate analog, a fluorophosphoramidate (FPA) functional group with characteristic P–F and P–N bonds. The stability of the FPA group was found to vary depending on the number of the amino group substitutions. Taking advantage of this intriguing molecular profile, gemcitabine FPA‐prodrug, which was designed to be efficiently converted to the corresponding monophosphate in cells, showed superior anticancer activity compared with the parent compound gemcitabine and its ProTide prodrug. More information can be found in the Research Article by Yuki Yoshida, Hiroshi Abe et al.